Evaluation of scoliosis in patients with lumbosacral transitional vertebra - Can, Tuba Selçuk (Journal of Surgery and Medicine, 2020)
Aim: Lumbosacral transitional vertebra and scoliosis both have the potential to alter spinal balance, along with psoas muscles, which are important in the maintenance of spinal alignment. In this study we aimed to evaluate the relationship between lumbosacral transitional vertebrae and their potential influence on lumbar alignment. Methods: In this cross-sectional study, lumbar Magnetic Resonance Imaging (MRI) studies that are referred to our Radiology Department between January 2017 and July 2017 were evaluated. 125 patients with lumbosacral transitional vertebra and 125 patients without any history of previous spinal surgery, trauma, inflammatory or infectious diseases were included. Type of transitional vertebra (unilateral/bilateral), presence of scoliosis and psoas muscle diameter-area measurements were evaluated. Results: Among the transitional vertebra group, 75 patients had unilateral and 50 had bilateral sacralization. Among sacralization patients, 52.8% also had scoliosis. The presence of scoliosis was significantly lower in patients with bilateral sacralization compared to those with unilateral sacralization (P=0.001). The psoas muscle cross-sectional area and diameters were also further evaluated for the presence of asymmetry in the scoliosis group. Measurements were made twice by one radiologist and the mean value was used for statistical analysis. Results showed that area and transverse diameter asymmetries were statistically significant in patients with scoliosis (P=0.001 and P=0.003, respectively). Conclusions: Lumbosacral transitional vertebra deteriorates spinal alignments and particularly when unilateral, may cause scoliosis and psoas muscle asymmetry. The pathophysiology of psoas muscle asymmetry, however, is controversial and should be further evaluated.